Book Review: Lyttleton, Chris. 2014: Intimate Economies of Development: Mobility, Sexuality and Health in Asia. (April 2018) - Wu, Camille S.
Lyttleton, Chris. 2014: Intimate Economies of Development: Mobility, Sexuality and Health in Asia . London and New York, NY: Routledge. xii + 215 pp. £110 (hardback). ISBN 978-0-415-81773-8.